An Efficient Micropropagation Protocol for Sugarcane viz. Isd 33 (Plant Tissue Culture and Biotechnology, 2025)
Six months' shoot tips of sugarcane variety Isd 33 were cultured on MS medium supplemented with different concentrations and combinations of plant growth regulators and coconut water for callus induction. The best (100%) callus formation was obtained on MS medium containing 3.5 mg/l 2, 4-D (2, 4-Dichlorophenoxyacetic acid) with 10% coconut water. Excellent multiple shooting with 100% shoot induction was observed when medium was supplemented with 1.5 mg/l BAP (6-benzylaminopurine) along with the combination of 1 mg/l Kn (Kinetin). However, the highest (6.86 cm) shoot length was found in 1 mg/l BAP with 1 mg/l Kn. The maximum number (18.83) of roots/shoot was recorded in 5 mg/l NAA (1-Naphthaleneacetic acid). The highest (4.42 cm) root length and maximum root initiation percentage (96.67%) were performed on rooting medium with 1 mg/l NAA in combination with 2 mg/l IBA (Indole-3-butyric acid).Plant Tissue Cult. & Biotech. 35(1): 21-31, 2025 (June)